Implementasi Metode Bilateral Filter Perbaikan Kualitas Citra RGB - Nurega Harahap (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
In the process of capturing images using a camera or other sensors often experience problems and deterioration in quality, such as capture results that are not as expected. This can happen because of the possibility of a camera lens that is not focused, the lighting settings are not perfect, the presence of dust or other dirt on the camera lens. Improving the quality of an image is necessary so that someone can observe the image clearly and in detail without any disturbance bilateral filter method is a filter that functions to replace The value of a pixel with the convolution calculation results in the area covered by the filter, this convolution operation is often involved in neighboring pixel operations. Which then produces software applications that are able to reduce the effects of disturbing noise on digital images with the bilateral filter method. With this method, it is expected to be able to solve the problem of image quality improvement in image improvement applications. This study discusses that the process undertaken to implement image improvement based on the bilateral filter method, then an application is built using MATLAB 2013 as an editor to edit programs.